Teaching Writing from the Teacher's discourse in a Chilean Bilingual School Context (Docentes 2.0 Journal, 2023)
The Chilean curriculum proposes the processual teaching of writing to achieve mastery of communicative competence in a language. The study's objective was to characterize and compare the teaching and evaluation process of writing in Spanish (mother tongue) and English (foreign language) in a Chilean school context. The research was based on the humanist paradigm through the case study method, following the qualitative approach of case study design and interpretative type. Eight teachers from a private bilingual educational establishment in Talcahuano, Chile, participated. They answered semi-structured interviews, and a content analysis was carried out in the Nvivo 12 software. The results indicated similarities in the didactic strategies for learning both languages. However, the differences lie mainly in giving feedback to the writing process.
Keywords: Teaching of writing; teacher discourse; bilingualism